2022
DOI: 10.1002/cncr.34405
|View full text |Cite
|
Sign up to set email alerts
|

Value of the prognostic nutritional index (PNI) in patients with newly diagnosed, CD5‐positive diffuse large B‐cell lymphoma: A multicenter retrospective study of the Huaihai Lymphoma Working Group

Abstract: BACKGROUND: CD5-positive diffuse large B-cell lymphoma (DLBCL) is a clinically rare subtype of DLBCL with aggressive clinical manifestations and a poor prognosis. It has been demonstrated that the prognostic nutritional index (PNI), an indicator of nutritional status and systemic inflammation, is a significant prognostic factor for several types of lymphoma. The objective of this multicenter retrospective study was to explore the prognostic value of the PNI in patients with CD5-positive DLBCL. METHODS: In tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Low PNI has been associated with poor OS and PFS in many cancers, including DLBCL. 18 , 42 , 43 Shen Z et al also found that PNI was a powerful predictor that could re-stratify the prognosis of different clinicopathologic subgroups. 43 In our study, the prognostic value of PNI was also verified, and we found that it can be used as an independent predictor of OS in patients with DLBCL to predict patient prognosis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Low PNI has been associated with poor OS and PFS in many cancers, including DLBCL. 18 , 42 , 43 Shen Z et al also found that PNI was a powerful predictor that could re-stratify the prognosis of different clinicopathologic subgroups. 43 In our study, the prognostic value of PNI was also verified, and we found that it can be used as an independent predictor of OS in patients with DLBCL to predict patient prognosis.…”
Section: Discussionmentioning
confidence: 98%
“… 18 , 42 , 43 Shen Z et al also found that PNI was a powerful predictor that could re-stratify the prognosis of different clinicopathologic subgroups. 43 In our study, the prognostic value of PNI was also verified, and we found that it can be used as an independent predictor of OS in patients with DLBCL to predict patient prognosis. We further compared the differences in clinicopathological characteristics between the high PNI group and the low PNI group, and found that the low PNI levels may reflect higher tumor load and greater aggressiveness, which may lead to malnutrition and immunosuppression and are associated with poorer survival outcomes in patients with DLBCL.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to tumors, researchers have expanded the application of the PNI to the prognosis of other diseases such as COPD, lung transplantation, dilated cardiomyopathy, and heart failure. In most studies, the ideal PNI threshold has been between 40 and 50 [ 24 ], such as 36.7 in patients with late-stage biliary tract cancer and 51 in patients with breast cancer [ 25 , 26 ]. This study explored the optimal threshold of 40.923 in elderly patients with acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…PNI was calculated from serum albumin levels and absolute lymphocyte counts, which was a comprehensive index re ected not only protein stores but also the immunological status. PNI plays a key role in assessing the prognosis of patients with a variety of diseases, including cancer, lymphoma, infectious diseases, and postoperative complications 11 . As an important component of PNI, serum albumin is an important antioxidant outside the cell.…”
Section: Discussionmentioning
confidence: 99%